PEMBERDAYAAN USAH MIKRO MELALUI PELATIHAN PENGEMBANGAN PRODUK DAN SALURAN PEMASARAN DIGITAL: Pelatihan olahan makanan, pelatihan branding dan pengemasan, serta pelatihan pengembangan marketplace. - M, Rudianto; Rahmawati; Dwi Amperawati, Endang; Djuminah; Marwanti; Hartoko, Sri; Noviani, Rita (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Microenterprises in Desa Sumber are small-scale household businesses run by the local community. Based on the existence of businesses, there are SMEs that produce processed food and batik cloth. In the processed food business, problems arise related to the absence of assistance and business management to develop, so that the community conducts small-scale and limited household businesses. Problems in the batik business are weak competitiveness, the number of batik products produced, and the lack of marketing expansion. The solution applied in this community service is micro business empowerment activities carried out through data collection, partnerships, ease of licensing, institutional strengthening and coordination with stakeholders. Food processing training, branding and packaging training, and marketplace development training were carried out.